Electoral Rules for Mayors and Incentives to Pork-Barrel: Quasi-Experimental Evidence from German Municipalities - Zohal Hessami (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper exploits a natural experiment in Hesse where a reform of the electoral rule from mayor appointment by the local council towards direct mayor elections was introduced during a phase-in period from 1993 to 1998. The end of the term of the last appointed mayor varies across municipalities for exogenous historical reasons and determines the timing of the switch in a particular municipality. Di fference-in-di fference estimations for 421 municipalities over the period from 1981 to 2010 reveal that municipalities with a directly elected mayor attract 5% more investment transfers from the state tier. This e ffect only materializes in the election year which suggests that mayors under the new electoral rule put more e ffort into grant applications for highly visible infrastructure projects in order to increase their re-election probability.
Keywords: D72; H72; H77; 330